Exploiting the Microhomology-Mediated End-Joining Pathway in Cancer Therapy - Patterson-Fortin, Jeffrey; D'Andrea, Alan D (Cancer research (Chicago, Ill.), 2020)
Repair of DNA double-strand breaks (DSB) is performed by two major pathways, homology-dependent repair and classical nonhomologous end-joining. Recent studies have identified a third pathway, microhomology-mediated end-joining (MMEJ). MMEJ has similarities to homology-dependent repair, in that repair is initiated with end resection, leading to single-stranded 3' ends, which require microhomology upstream and downstream of the DSB. Importantly, the MMEJ pathway is commonly upregulated in cancers, especially in homologous recombination-deficient cancers, which display a distinctive mutational signature. Here, we review the molecular process of MMEJ as well as new targets and approaches exploiting the MMEJ pathway in cancer therapy.